2016
DOI: 10.21927/jnki.2015.3(2).116-122
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Ekonomi dan Motivasi Ibu dalam Pemberian ASI Eksklusif pada Bayi Usia 0-6 Bulan di Bidan Praktek Swasta (BPS) Ummi Latifah Argomulyo, Sedayu Yogyakarta

Abstract: <p>Profile of Indonesian health in 2013 showed that the percentage of exclusive breastfeeding in infants aged 0-6 months is about 61.5%. The low level scope exclusively breastfeeding can not be separated from some factors affecting and one of them is a mother motivation to give exclusively breastfeeding to their baby. The other factors affecting breastfeeding are the socio-culture economy (formal education mother, family income and status working mother). The purpose of this study was to know the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
3
3
0
14
Order By: Relevance
“…Results showed that the mother's work status was mostly in the category of mothers who did not work, which amounted to 69.6% while the category of mothers who worked was 30.4%. The results of this study are in line with the research conducted by Maulida et al (2015) that most mothers are mothers who do not work, which is 56.3% while mothers who work are 43.7%. The results of this study are also in line with the research conducted by Tewabe et al (2017) in Ethiopia that the majority of mothers belong to the category of mothers who do not work, which is 79.6% while the category of mothers who work is 20.3%.…”
Section: Maternal Employment Statussupporting
confidence: 91%
“…Results showed that the mother's work status was mostly in the category of mothers who did not work, which amounted to 69.6% while the category of mothers who worked was 30.4%. The results of this study are in line with the research conducted by Maulida et al (2015) that most mothers are mothers who do not work, which is 56.3% while mothers who work are 43.7%. The results of this study are also in line with the research conducted by Tewabe et al (2017) in Ethiopia that the majority of mothers belong to the category of mothers who do not work, which is 79.6% while the category of mothers who work is 20.3%.…”
Section: Maternal Employment Statussupporting
confidence: 91%
“…Hal ini juga sejalan dengan penelitian Maulida (2015), yang menyatakan bahwa ibu dengan tingkat ekonomi yang tinggi memiliki kemungkinan 0.33 lebih kecil untuk memberikan ASI eksklusif daripada ibu dengan tingkat ekonomi yang rendah. Hasil penelitian ini sejalan dengan penelitian Agustina et al (2012) menyebutkan bahwa tingkat kekayaan seorang ibu berpengaruh terhadap pemberian ASI eksklusif.…”
Section: Pengaruh Pendapatan Keluargaunclassified
“…Hasil uji statistik dengan chi square test menunjukkan bahwa ada hubungan antara motivasi intrinsik dengan pemberian ASI eksklusif dengan nilai p (sig) 0,024 < 0,05. Hasil penelitian (Maulida, 2013), menyatakan bahwa sebagian besar responden memiliki motivasi dalam memberikan ASI eksklusif pada bayi usia 0-6 bulan berada pada kategori sedang yaitu sebanyak 21 responden (43,7%), dan sebagian kecil responden memiliki motivasi tinggi yaitu sebanyak 13 responden (27,1%) (7).…”
Section: Hubungan Motivasi Intrinsik Dengan Pemberian Asi Eksklusif Dunclassified